(untitled) (Academicia Globe: Inderscience Research, 2021)
The article deals with the importance of didactic principles in labor education, students set clear goals, the phenomenon, the process and the relationship between them, the rules for the operation of these principles in pedagogical practice, the formation of skills and abilities of students in the learning process, increasing student interest, information on how to help you remember the desired lesson well.